Quantification of pre-competitive sleep/wake behaviour in a sample of South African cyclists - Steenekamp, Travis (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2018)
The quantification of athlete pre-competitive sleep behaviour is of interest owing to the possibility that sleep loss may have a negative effect on health and performance. The purpose of this study was to monitor and quantify the sleep/wake patterns of South African cyclists prior to competitive races. A total of 336 cyclists, male and female and of differing competition levels, cycling in either the 2015 Tsogo Sun Amashova or the 2016 Telkom 94.7 Cycle Challenge completed an altered version of the Competitive Sports and Sleep Questionnaire. The questionnaire asked cyclists to report on precompetitive sleep over the past year. A subset of 92 cyclists also recorded a Core Consensus Sleep Diary for the three nights leading up to the races. The questionnaire showed that 67% of the cyclists reported worsened sleep at least once prior to competition within the past 12 months. The sleep diary found that the cyclists' average sleep duration the night before the races was 6h19min (Â±1h38min), which was significantly less than two and three nights prior to the races. Sleep quality was also shown to deteriorate significantly the night before the races. The contributing factors leading to worsened pre-competitive sleep were the time the cyclists had to wake-up as well as perceived increases in sleep latency and awakenings after sleep onset. Anxiety was found to be the major cause of sleep disturbances. While females were found to be significantly more likely to report having experienced poorer sleep before competition in the past year, the sleep diary showed no difference in sleep the night before the races between the sexes. Females were significantly more likely to report instances of unpleasant dreams and waking up during the night. Again, the sleep diary data did not corroborate these findings. Females were also found to report significantly more accounts of nervousness or thoughts about competition as being the cause of sleep problems. There was no difference in sleep loss the night before competition when comparing competition-level groups. The only significant difference was that recreational cyclists were more likely to report sleeping in foreign environments as a cause of sleep disturbances. Despite a large percentage of cyclists experiencing pre-competitive sleep loss, over half (55%) perceived sleep loss to have no impact on their performance. Analysis of pre-sleep behaviour also revealed that the cyclists engaged in several practices that may have a negative effect on subsequent sleep. The vast majority of the cyclists (61%) indicated having no specific strategy to help them sleep the night before competition. Fifteen percent of cyclists reporting using media devices to help them fall asleep, a practice that has been shown to disrupt sleep. In conclusion, most cyclists, regardless of sex and level of competition experience precompetitive sleep loss attributed largely to anxiety but with the perception that this loss in sleep does not negatively impact their performance.
Keywords: Sleep deprivation; Cyclists Health and hygiene -- South Africa; Sleep Physiological aspects; Performance; Performance anxiety